2021
DOI: 10.1016/j.jlr.2021.100104
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease stratification by liver lipidomics

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 85 publications
2
36
0
Order By: Relevance
“…(D) The MBOAT7 product, 38:4 PI, measured in (21), is negatively associated with total NAFLD activity score (NAS). (E) Total PI, measured in (21), is negatively associated with total NAS. Data presented as mean ± SD, analyzed by one-way ANOVA with Tukey’s post-hoc correction for multiple comparisons, * p < 0.05, **** p < 0.0001.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(D) The MBOAT7 product, 38:4 PI, measured in (21), is negatively associated with total NAFLD activity score (NAS). (E) Total PI, measured in (21), is negatively associated with total NAS. Data presented as mean ± SD, analyzed by one-way ANOVA with Tukey’s post-hoc correction for multiple comparisons, * p < 0.05, **** p < 0.0001.…”
Section: Resultsmentioning
confidence: 99%
“…We also mined publicly available lipidomic analyses for PI measured in human NAFLD/NASH compared to control livers. These included data deposited in Metabolomics Workbench ST000915 (20), as well as supplemental data from an open access publication (21). Total PI levels as well as the predominant arachidonoylated PI species (38:4), were assessed in a total of 80 NC livers, 51 HO livers, 160 NAFL livers, and 134 NASH livers.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of quantitative proteome information could further improve the performance of our enrichment algorithm presented in this paper and open up the possibility to directly identify causal proteins. This but could be of great value for the causal interpretation of lipidome changes, which would directly translate into relevance for clinical applications, due to the many associations of lipids with various disorders [27, 38, 29, 59, 63].…”
Section: Discussionmentioning
confidence: 99%
“…For a detailed description, please refer to the Methods section. Additionally, studies sometimes report individually identified (but not quantified) molecular species [63]. These can be used as input for LINEX to refine the network extension.…”
Section: A Framework For Lipid Network Analysesmentioning
confidence: 99%
See 1 more Smart Citation